Synthesis and Kinetic Model of Oleic Acid-based Epoxides by In Situ Peracid Mechanism - Intan Suhada Azmi; Muhammad Hazim Abu Bakar; Danial Nuruddin Azlan Raofuddin; Hamzah Hafizuddin Habri; Mohamad Heiry Mohd Azmi; Mohd Jumain Jalil (Kemija u Industriji, 2022)
The global consumption of raw materials has shifted from the use of non-renewable materials to renewable materials. Studies on greener epoxidation by using vegetable oils to produce eco-friendly epoxides have also increased. In this study, the epoxidation of palm oleic acid was carried out by in situ generated performic acid. Fourier transform infrared spectroscopy of the products was conducted to confirm the success of the epoxidation. Lastly, a mathematical model was developed using the numerical integration of the 4th order Runge–Kutta method, and the results showed good agreement between the simulation and experimental data, which validates the kinetic model.